Implementation of the Independent Curriculum in Arabic Language Learning at SMP IT Bina Insani Kayuagung - Muhklis, M Sholahuddin; Machmudah, Umi Machmudah; Munjiah, Ma'rifatul (An Naba, 2025)
Arabic language learning at the junior high school level often faces challenges such as low student interest and limited resources. This study analyzes the implementation of the Independent Curriculum in Arabic language learning at Bina Insani Integrated Islamic Junior High School (SMP IT) in Kayuagung. The aim of this research is to identify the supporting and inhibiting factors in implementing this curriculum at Islamic junior high schools. Using a qualitative case study approach, data were collected through observations, interviews, and document analysis involving the Vice Principal of Curriculum Affairs and Arabic language teachers. The findings reveal that the implementation of the Independent Curriculum in Arabic learning is supported by several factors, including the availability of school facilities, diverse teaching methods, teacher training, and the flexibility of the curriculum. However, several challenges were also identified, such as limited textbooks, difficulties in teacher adaptation, frequent teacher turnover, and low student motivation in learning Arabic. To enhance the effectiveness of Arabic language learning, the study recommends providing textbooks aligned with the curriculum, strengthening teacher training, increasing extracurricular activities, and improving teacher retention strategies. These efforts are expected to optimize Arabic language education and ensure alignment with the goals of the Independent Curriculum.